Analysis of SI PENDEKAR Implementation with Technology Acceptance Model at Dr. Soedono General Hospital - Abdul Rohim; Ansarul Fahrudda; Heru Suswojo; Pipit Festi Wiliyanarti (KHD Production, 2025)
Health information systems are important in providing efficient and effective services in the era of rapid development of information technology today. This study analyzed healthcare workers' acceptance of the benefits of implementing the Integrated Outpatient Revisit Patient Service Information System (SI PENDEKAR) at the outpatient clinic in Dr. Soedono General Hospital. This study used quantitative analysis with a cross-sectional approach. The questionnaire used a Technology Acceptance Model (TAM) instrument to evaluate officer acceptance of SI PENDEKAR innovation. The research subjects included 30 healthcare workers related to the use of innovation on officers’ attitudes towards using (path coefficient = 0.578, p=0.001) and perceived usefulness on behavioral interest in using (path coefficient = 0.651, p =0.001). The healthcare worker’s perception of the benefits of this innovation will increase the attitude of acceptance and attitude of use, which can increase the speed of services in the outpatient clinic.